The effectiveness of observe and remember game to students' vocabulary mastery - Cahyati; Yuli Puji Astutik; Surti Milarisa (Relawan Jurnal Indonesia, 2020)
Vocabulary is a fundamental aspect of learning English. It is interconnected to four English skills, speaking, reading, listening, and writing. It is also interrelated to pragmatics and discourse. Without mastering vocabulary, someone would not be able to express oral and written language. Therefore, English teachers need to have good qualifications in teaching vocabulary to make their class more fun and interesting. Besides, they also need to teach the vocabulary in context so that the students will not lose the exact meaning of the vocabulary they have learned which caused misunderstanding during communication. Therefore, this study aimed to analyze the effectiveness of Observe and Remember Game on students’ vocabulary mastery. The writers applied some procedures namely pretest, treatment by using Observe and Remember game then conducting the posttest after applying the game. To analyze the data, t-test was applied using using SPSS to get the mean scores. From the result of the statistical calculation, the average score of the pretest was 49.82, the result of the posttest was 68.46. It increased by 18.64%. It could be summarized that Observe and Remember game was effective on students’ vocabulary mastery.